An Analysis of Teachers’ Questions in English Classroom Activity Based on HOTS in SMAN Kota Padang - Rafika Ramadhani; Yetti Zainil (Universitas Negeri Padang, 2019)
In EFL context mostly, teachers pose questions to check students’ understanding and stimulate students’ curiosity. There are many types of questions that can be asked by teachers. Each question gives a different influence on students’ thinking levels. This research was intended to analyze the most types of questions asked by teachers in EFL classroom activity in SMAN Kota Padang. Also, the common levels of questions asked by teachers in EFL classroom activity in SMAN Kota Padang. This research is descriptive qualitative research. It involved observing and describing the behaviour of a subject without influencing it in any way. The subjects of this research were 12 teachers from 4 schools selected by using random sampling technique. The techniques of data collection were classroom observation-video recordings and stimulated recall interview (SRI) recordings. The findings of this research are the most type of questions asked by teachers in EFL classroom activity in SMAN Kota Padang is display question with 575 questions (82.85 % of the total questions). Thus, the common level of questions asked by teachers in EFL classroom activity in SMAN Kota Padang is remembering (C1) category, which is the lowest level of thinking in cognitive domain.